Perbandingan Buyback Stock Perusahaan Swasta dan Perusahaan Badan Usaha Milik Negara (BUMN) saat Pandemi Covid-19 - Mohammad Arridho Nur Amin; Dewi Indriasih; Catur Wahyudi (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to analyze the differences between the Abnormal Stock Returns Trading Volume Activity of private and state-owned companies before and after the announcement of stock buybacks in the midst of the Covid-19 pandemic. The samples used were private companies and BUMN that carried out Buyback Stock during the Covid-19 pandemic. This research uses secondary data in the form of daily company stock price data, daily company trading volume data, as well as outstanding share data from private companies and BUMN listed on the Indonesia Stock Exchange. The calculation of expected return uses the Market Adjusted Model method. Testing the hypothesis using the paired sample t-test difference test. The results of this study are sig. (tailed) on the abnormal return variable, the probability value is greater than 0.05 (0.080 and 0.893 > 0.05) or the average cumulative abnormal return of private companies is greater than the average. Abnor¬¬mal cumulative stock returns of BUMN companies. On the trading volume activity variable, the results show the TVA significance value is smaller than 0.05, namely 0.043 and 0.43. so that it is stated that the cumulative average trading volume activity of BUMN companies is greater than the average cumulative trading volume activity of private companies